EFFECT OF CUTWORM POPULATION AND SHOOT DAMAGE IN POTATO ON THE TUBER YIELD - Sharma, Sanjay K (Potato Journal, 2013)
The predictive regression equations worked out between yield of healthy potato tubers and cutworm population/ shoot damage at 14 days after first and second spray (DAS1 and DAS2, respectively), when the spray was initiated at economic threshold level (ETL), revealed negative correlation with high value of coefficients of determination (R2). Contrarily, the equations obtained by regressing yield of healthy potato tubers on cutworm population/shoot damage at pre-treatment, showed negative correlation with low values of R2. These regression equations suggested that the cutworm population and shoot damage that occurred after pest reached ETL had more potential in reducing the yield of healthy tubers and increasing the yield of damaged tubers as compared to that before ETL.